2022
DOI: 10.1080/21645515.2022.2114699
|View full text |Cite
|
Sign up to set email alerts
|

COVID-19 vaccine acceptance rate and its predictors in Ethiopia: A systematic review and meta-analysis

Abstract: Coronavirus disease (COVID-19) is a global pandemic caused by the SARS-CoV-2 virus. COVID-19 vaccine is the best strategy for prevention. However, it remained the main challenge. Therefore, this systematic review and meta-analysis aimed to determine the overall pooled estimate of COVID-19 vaccine acceptance and its predictors in Ethiopia. Consequently, we have searched articles from PubMed, EMBASE, Web of Science, Google Scholar, reference lists of included studies, and Ethiopian universities’ research reposit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
19
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(24 citation statements)
references
References 56 publications
5
19
0
Order By: Relevance
“…This nding is in line with the study conducted in Wolaita Sodo town [27], in Gurage Zone [3], systemic review and meta-analysis Ethiopia [42]. The possible reasons could be health education, burden of disease and rst priority was given for individual with chronic disease to be vaccinated rst.…”
Section: Factors Associated With Willingness To Accept Covid-19 Vaccinesupporting
confidence: 84%
See 1 more Smart Citation
“…This nding is in line with the study conducted in Wolaita Sodo town [27], in Gurage Zone [3], systemic review and meta-analysis Ethiopia [42]. The possible reasons could be health education, burden of disease and rst priority was given for individual with chronic disease to be vaccinated rst.…”
Section: Factors Associated With Willingness To Accept Covid-19 Vaccinesupporting
confidence: 84%
“…In this study, clients with good knowledge were 2 times more likely willing to accept COVID-19 vaccine than those with poor knowledge. This is consistent with systematic review and meta-analysis in East Africa [31], in Ethiopia [42], North East Ethiopia[26], southern Ethiopia among adult population [3] and southern Ethiopia on lactating mothers [25].The possible explanation could be those who had awareness of the vaccine might know the bene t of being Vaccinated such as halting the transmission of new COVID-19 infections and preventing the Possibility of further morbidity and mortality caused by infections.…”
Section: Factors Associated With Willingness To Accept Covid-19 Vaccinesupporting
confidence: 83%
“…Few studies conducted in Ethiopia recently utilized limited number of studies, and missed some variables like attitude of the public towards the vaccine uptake (11)(12)(13)(14). A number of associated factors were identified so far regarding the willingness of people to take COVID-19 vaccines; perceived susceptibility, safety (fear of side effects), willingness to pay for the vaccine, history of contracting COVID-19, knowledge regarding COVID-19, sex, occupation, religion, age and marital status (9,15,16).…”
Section: Introductionmentioning
confidence: 99%
“…However, studies have shown that the acceptance and uptake rate of COVID-19 vaccination among chronic disease populations are relatively lower than the expected standards. 23–37 …”
Section: Introductionmentioning
confidence: 99%
“…Previous studies with inconsistent findings revealed that populations with chronic diseases had a higher probability of accepting the COVID-19 vaccine in Ethiopia. 23 , 25 , 31 , 38–40 However, there have been no pooled measures for the COVID-19 vaccine acceptance by patients with chronic diseases in Ethiopia. In addition, primary studies have shown that the association of knowledge and attitude toward the COVID-19 vaccine acceptance among patients with chronic diseases had inconsistent findings in Ethiopia.…”
Section: Introductionmentioning
confidence: 99%